Penguatan Nilai Mumalah Melalui Progam Kultum Tarawih Dalam Meningkatkan Kehidupan Beragama Masyarakat - Munawaroh, Imroh Atul; Ayuningtyas, Sekar Arum; Muchlisin, Muhammad; Kawakib, Kawakib; Lutfi, Lala Khoironi (Assoeltan: Indonesian Journal of Community Research and Engagement, 2026)
Muamalah is an important part of Islamic teachings that regulates social and economic aspects. However, the people of Joho Village still have a lack of understanding of these values. This community service activity aims to improve the quality of religious life of residents by strengthening their understanding of muamalah values. In compiling this research, students from the Riyadlotul Mujahidin Ngabar Ponorogo Islamic Institute Community Service Program used a simple, seven-minute sermon (kultum) da'wah method that took place daily after tarawih prayers in Joho Village, Wonogiri. The approach used was descriptive qualitative to explain the phenomenon of value improvement in a structured manner. The findings from this community service indicate that the kultum program can significantly increase community understanding and encourage changes in social and economic attitudes that are more aligned with Islamic principles. The conclusion of this community service is that the kultum program after tarawih is an efficient, easily accepted, and applicable da'wah strategy in improving the quality of religious life and the integrity of muamalah among the people of Joho Village.